2016
DOI: 10.1107/s2052252516008423
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and evolution of labile sulfur allotropesviakinetic encapsulation in interactive porous networks

Abstract: Reported here are the isolation and direct observation of extremely reactive S2 and its conversion into bent-S3 via a cyclo-S3 2+ intermediate on interactive sites in porous coordination networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…This approach to visualising sulphur allotropes was later refined using a new framework comprised of CuI and tetra-4-(4pyridyl)phenylmethane (tppm). 45 The porous [(CuI)2(tppm)]n framework, coupled with a gentler means of generating and transferring sulphur vapour, allowed the first direct crystallographic characterisation of small sulphur allotropes. The identity of the allotrope was found to change with temperature, with metastability of linear S2 and cyclic S3 observed at 250 and 300 K, respectively (Fig.…”
Section: Gas-phase and Volatile Reagent Studiesmentioning
confidence: 99%
“…This approach to visualising sulphur allotropes was later refined using a new framework comprised of CuI and tetra-4-(4pyridyl)phenylmethane (tppm). 45 The porous [(CuI)2(tppm)]n framework, coupled with a gentler means of generating and transferring sulphur vapour, allowed the first direct crystallographic characterisation of small sulphur allotropes. The identity of the allotrope was found to change with temperature, with metastability of linear S2 and cyclic S3 observed at 250 and 300 K, respectively (Fig.…”
Section: Gas-phase and Volatile Reagent Studiesmentioning
confidence: 99%
“…Thus far, redox‐active ligands with one redox center have been most commonly used for building redox‐active coordination networks . On the other hand, we have demonstrated the importance of interactive sites for the generation of unique properties, such as guest encapsulation, trapping unstable species, and chemical transformations . Hence, we aimed to prepare an interactive ligand that features multiple redox‐active centers capable of producing mixed‐valence (MV) states .…”
Section: Figurementioning
confidence: 99%
“…[4a, 8] On the other hand, we have demonstrated the importance of interactive sites for the generation of unique properties,s uch as guest encapsulation, [9] trapping unstable species, [10] and chemical transformations. [11] Hence,w ea imed to prepare an interactive ligand that features multiple redox-active centers capable of producing mixed-valence (MV) states. [12] Organic MV ligands may serve as an ew functional component for coordination networks,b ut, to the best of our knowledge,r eports on coordination networks composed of such MV ligands remain elusive.…”
mentioning
confidence: 99%
“…We demonstrated that kinetic assembly of a rigid T d ligand, tetra­(4-pyridyl)­phenylmethane (4-TPPM; Figure a) and a labile CuI cluster generates a thermally stable coordination network with single interactive iodide sites in the pores. X-ray structure analysis revealed that the interactive iodide can form chemical bonds with I 2 or reactive sulfur species like S 2 and S 3 . The Cu site retains the tetrahedral geometry over the guest encapsulation because a pyridine ring in 4-TPPM can rotate to hamper any interactions with guest molecules. Here, we report the synthesis of a porous coordination network with dual interactive sites in a pore by suppressing the rotational motion of pyridyl rings using a tetra­(3-pyridyl)­phenylmethane (3-TPPM) ligand (Figure b).…”
Section: Introductionmentioning
confidence: 99%